THE STUDY OF ORGANIZING MEETING IN EDUCATIONAL QUALITY ASSURANCE COMMITTEES, PHRANAKHON RAJABHAT UNIVERSITY - Phuttanawong, Papichayaporn; Khumsumrit, Suchittra (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2025)
This research aimed to (1) to study the result of Organizing Meeting in Educational Quality Assurance Committees, Phranakhon Rajabhat University and (3To study opportunities to develop meeting organizing guidelines of the Educational Quality Assurance Committee, Phranakhon Rajabhat University. The mixed research methods were utilized in the study. The target group is members of educational quality assurance committee of Phranakhon Rajabhat University. For the quantitative methodology, the target group is 67 people were requested to answer the questionnaires and analysis by statistical analysis. For the qualitative methodology, 12 people were interviewed and analyze by Content analysis. Findings: 1) The effectiveness of organizing meetings of the Educational Quality Assurance Committee, Phranakhon Rajabhat University, was found in the following five aspects: (1) Achieving the goals: It was found that the meeting was organized with appropriate agenda items every time, in accordance with the objectives of university education quality assurance. (2) Procedures: It was found that the meeting was organized in a proper manner and was held in accordance with the meeting regulations. (3) Timing: It was found appropriate, concise, timely and allows participants to express their opinions freely. (4) Cost: It was found that very worthwhile to hold the meeting as it is currently being held online. (5) Accuracy: It was found that Tthe content is accurate and clear. The documents are easy to read and understand. 2) There are three stages for the procedures and organization of the meetings of the Educational Quality Assurance Committee in Phranakhon Rajabhat University. (1) (Before the meeting) It was found that the meeting invitation letter was sent before the meeting was scheduled and that information technology equipment was prepared to support the meeting. (2) (During the meeting) it was found that there were procedures for operations that followed the meeting documents and were able to allow meeting participants to express their opinions on the issues that they wanted to present. (3) (After the meeting) it was found that there was a person responsible for supervising and following up on the work assigned by the meeting according to the specified time. 3) Developing an effective meeting format for the Education Quality Assurance Committee found that online meetings should be used in conjunction with onsite meetings, and the time should be appropriately compacted.